2020
DOI: 10.1186/s41927-019-0104-5
|View full text |Cite
|
Sign up to set email alerts
|

Dual energy CT findings in gout with rapid kilovoltage-switching source with gemstone scintillator detector

Abstract: Background: A definite diagnosis of gout requires demonstration of monosodium urate crystals in synovial fluid or in tophi, which in clinical practice today seldom is done. Dual energy CT (DECT) has repeatedly been shown to be able to detect monosodium urate crystals in tissues, hence being an alternative method to synovial fluid microscopy. The vast majority of these studies were performed with CT scanners with two X-ray tubes. In the present study we aim to investigate if and at what locations DECT with rapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…Based on these advantages, the DECT urate scoring system should be widely applyed in clinical practice. Patients with higher volumes of MSU crystal deposits are likely to develop joint [20] As our results showed, some studies demonstrated that the total DECT urate score was highly positively correlated with urate deposit volumes. [13] Some studies have applied this urate scoring system and observed that a higher total urate score is closely associated with longer disease duration and bone erosion.…”
Section: Discussionsupporting
confidence: 70%
“…Based on these advantages, the DECT urate scoring system should be widely applyed in clinical practice. Patients with higher volumes of MSU crystal deposits are likely to develop joint [20] As our results showed, some studies demonstrated that the total DECT urate score was highly positively correlated with urate deposit volumes. [13] Some studies have applied this urate scoring system and observed that a higher total urate score is closely associated with longer disease duration and bone erosion.…”
Section: Discussionsupporting
confidence: 70%
“…Furthermore, the results of our study also showed that the total urate deposit score was higher in patients with longer disease duration and correlated strongly to the presence of tophus, bone erosion, and disease duration. Similarly, Svensson et al [31] applied this urate scoring method and found that the amount of MSU deposits is associated with the presence of tophus and disease duration. Dalbeth et al [26] found that higher urate deposits are correlated with tophi and bone erosion.…”
Section: *P Value Was Calculated By Fisher Exact Testmentioning
confidence: 99%
“…One limitation of our study is that the DECT scoring was performed by only one reader, but this reader is an experienced radiologist who scored all images. Prior work has demonstrated good intra-reader agreement using the DECT scoring system [ 20 ]. Further, the lack of a control group does not allow causal inferences.…”
Section: Discussionmentioning
confidence: 99%